The Measurement of Heparin - Denson, K. W. E; Bonnar, John (Thrombosis and Haemostasis, 1973)
A method for the measurement of heparin utilising the potentiating effect of heparin on the action of anti-factor Xa is described. The effect on the assay of platelet contamination of plasma, the presence of fibrinogen degradation products and low levels of anti-factor Xa have been studied. The assay method has been compared with the calcium thrombin time method and a group of obstetrical patients have been studied using both methods.